Concepções históricas e políticas da formação de professores no Brasil: um enfoque sobre as políticas dos governos FHC e LULA - Oliveira, Kalina Gondim de (2016)
The study aims to identify the teacher training policies in the neoliberal governments in Brazil, with special focus on the governments of Fernando Henrique Cardoso - Cardoso and Luiz Inacio Lula da Silva - Lula; and analyze them in the context of contemporary Brazilian education. It sets a time frame in the case of the two governments, the period between 1995 and 2010, in view of the object of study. This is bibliographic and documentary research study which uses as analytical reference the historical materialist dialectics because it is a theory of knowledge able to explain the reality, expose the contradictions and point out the possibilities of overcoming. The data indicate that the training policy overcoming possibilities. The data indicate that teacher training policies in the analyzed scenario appear to be fragmented, decontextualized, under the yoke of capital. In this perspective, questioning the practices of teachers, their ways to be and act now stabilized, the methods used, the valuation models and curricular organization, under the emergence of new paradigms in education. This study points to the contradictions evident in teacher training, as it believes that this process can not ignore the question of class struggle and the historical denial of knowledge workers who, in this case, are the teachers of basic education, which makes the problem even more aggravating, since these, in most cases, will have as a workplace to public school, an institution that has the school population the children of the working class.